Sociological Reflections on the Interaction Between Teenagers’ Psychological Development and Social Media - Li, Ziyan (Transactions on Social Science, Education and Humanities Research, 2026)
In recent years, with the development of society in an era of digitalisation, the lives of teenagers have gradually been altered by changes in social networks. This paper will examine the all-around changes in society that have occurred as a result of this phenomenon, and investigate the effects on the self-concept, group dynamics and psychological well-being of teenagers online. Based on studies of related research and established theories in sociology, this paper will present the dualistic function of social media platforms at present: promoting global communication to an unprecedented extent and causing mental health problems. Based on the above research, although these virtual environments provide space for self-expression and community construction for young people, there are also certain risks, such as cyberbullying, extended social comparison, and pressure to build an online persona. The development of these platforms has been too rapid for the construction of traditional social control mechanisms, and as a result, adolescents are more exposed to new types of digital stress. Given the structural inequalities in digital access and literacy, this paper will also investigate the worsening digital divide and how it affects the unequal distribution of social capital among young people. The above discussions show that not all people have the same mental health problems caused by social media; they are also different due to factors such as socio-economic background and gender. Finally, the paper puts forward a balanced view based on sociology and proposes to strengthen digital literacy education for young people, improve the role of parents in supervision, and build ethical platforms to promote all-round healthy growth for young people in the digital age.